On the rails of capital: Industrial engineers and railways in Sao Paulo at the beginning of the 20th century - Martins da Silva, Henry Marcelo [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2018)
This research seeks to understand the action of a group of industrial engineers of Sao Paulo at the beginning of the 20th century, in a context of intense transformations promoted by the insertion of the State in the coffee complex. Taking advantage of the moment of expansion of the economy, of urbanization and development of publ is services and growth of the capital market, a group of industrialists, headed by the engineer Alvaro de Menezes, collectively undertook a series of investments and businesses that culminated, at the end of the first decade of the last century, with the control of four Sao Paulo railway companies: the E. F: Araraquara, the E. F. Dourado, the E. P: Sao Paulo-Goyaz and the E.F Pitangueiras. Owners of the majority of the shares and lords of the destinies of the companies, they articulated large loans in the country and abroad, generating a deficit left for shareholders and suppliers that culminated in the bankruptcy of the four companies in 1914. From sources such as Annual Reports of the railways and several newspapers of the period, the research intends to understand the conditions that allowed the group's actions in the control of the railroads, besides identifying the strategies of the group of industrial engineers who, as specialists in the works of the big company of public services, acted aggressively to secure private benefits.
Keywords: engineers; urbanization; railways; capital market